The ProtekDuo for percutaneous V-P and V-VP ECMO in patients with COVID-19 ARDS. Issue 12 (December 2022) - El Banayosy, Ahmed M; El Banayosy, Aly; Brewer, Joseph M; Mihu, Mircea R; Chidester, Jaclyn M; Swant, Laura V; Schoaps, Robert S; Sharif, Ammar; Maybauer, Marc O
Objective: The ProtekDuo with oxygenator mimics veno-venous (V-V) extracorporeal membrane oxygenation (ECMO) in veno-pulmonary (V-P) configuration. We have recently developed a new configuration by utilizing a 25 Fr multistage femoral venous drainage cannula and by returning oxygenated blood through both lumina of the double lumen ProtekDuo cannula (V-VP configuration), thereby creating partial right ventricular bypass and oxygenated blood flow of up to seven LPM. We investigated our experience with V-P and V-VP ECMO in patients suffering from COVID-19 acute respiratory distress syndrome (ARDS). Methods: Single center, retrospective observational study. Results: Of nine patients, one was initiated on V-A, two on V-P, and six on V-V ECMO. All patients were reconfigured to V-P and five patients in addition had V-VP ECMO configuration. All patients had at least one and up to three circuit exchanges. Patients were on ECMO support between 20 and 122 (55 ± 29) days, were in ICU between 46 and 161 (78 ± 40) days with a total hospital length of stay between 35 and 171 (82 ± 42) days. Six of nine (67%) patients could successfully be weaned off ECMO, survived, and were discharged. Conclusion: The ProtekDuo cannula in V-P configuration provides ECMO blood flow while reducing RV flow, wall-stress and dilatation, as well as oxygen consumption. The V-VP configuration is useful to provide high blood flows of up to seven LPM of oxygenated blood, and partial RV support without over-circulating the pulmonary vascular bed. Our results show that V-P and V-VP ECMO configurations are feasible, have good outcome and are without complications.